UNICEF - Connolly, Sean, 1956- (Mankato, Minn. : Smart Apple Media, 2009)
Describes the history of the United Nations Children's Fund and their efforts since 1946 to help the world's children through humanitarian aid, education, and medical care.
Giving children a chance -- Wars and peace -- Framework for help -- Reporting to the world -- The thick of things -- A team player -- Closer to home -- Looking ahead -- Young voices.
"A+.".
Includes bibliographical references (p. 45) and index.
5.6
5-8
Keywords: UNICEF -- Juvenile literature; UNICEF; UNICEF